Evaluation of Natural Extracts as Promising Components of Bioactive Coatings for Orthopedic Implants - Kravanja, Katja Andrina; Finšgar, Matjaž; Knez, Željko; Knez Marevci, Maša (Frontiers in Materials, 2022)
The development of drug-eluting bioactive coatings for orthopedic implants has gained increased interest in recent years with an intent to reduce postoperative complications and improve tissue regeneration at the implant interface. Due to the remarkable benefits of natural polyphenolic components, such as antioxidant, antimicrobial, anti-inflammatory, anti-cancer and bioactive activity, and their ubiquitous availability in nature, they are promising candidates for incorporation into bioactive coatings of advanced medical devices in future clinical applications. However, further research is needed to address all challenges. This review aims to highlight the prosperity of natural compounds widely available in nature loaded in implantable devices, summarize the ”state of the art” in this field, identify the challenges, and accordingly suggest the optimal preparation methods and characterization.